2007
DOI: 10.1038/sj.ijo.0803523
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of adaptive thermogenesis

Abstract: The epidemic of obesity is developing faster than the scientific understanding of an efficient way to overcome it, as reflected by the low success rate of short-and long-term weight loss interventions. From a clinical standpoint, this suggests that the body tends to defend a set point of possible genetic origin in the context of a weight-reducing program. As described in this paper, this limited therapeutic success may depend on adaptive thermogenesis, which represents in this case the decrease in energy expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 94 publications
4
99
0
6
Order By: Relevance
“…These data indicate that CART À1336 delA, PPARG2 1431 C4T and IGF2 Apal A4G may be involved in adaptations in thermogenesis independent of body composition. 7 The present finding that PPARG2 1431 C4T increased postprandial REE, together with an earlier report showing that individuals with the Pro12Ala polymorphism of PPARG2 had an increased postprandial REE and higher satiety, 26 suggest that PPARG2 polymorphisms may play a role in postprandial REE. The association between IGF2 Apal A4G and postprandial REE became statistically nonsignificant when further adjusted for postprandial plasma insulin concentration.…”
Section: Postprandial Reesupporting
confidence: 48%
See 2 more Smart Citations
“…These data indicate that CART À1336 delA, PPARG2 1431 C4T and IGF2 Apal A4G may be involved in adaptations in thermogenesis independent of body composition. 7 The present finding that PPARG2 1431 C4T increased postprandial REE, together with an earlier report showing that individuals with the Pro12Ala polymorphism of PPARG2 had an increased postprandial REE and higher satiety, 26 suggest that PPARG2 polymorphisms may play a role in postprandial REE. The association between IGF2 Apal A4G and postprandial REE became statistically nonsignificant when further adjusted for postprandial plasma insulin concentration.…”
Section: Postprandial Reesupporting
confidence: 48%
“…When, in addition to FFM, age, sex and research centre, postabsorptive REE was adjusted for FM, HSD11B1 G4A, GAD2 À243 A4G and LIPC 644 A4G remained significantly Genetics and energy expenditure GH Goossens et al associated with postabsorptive REE. These data suggest that HSD11B1 G4A, GAD2 À243 A4G and LIPC 644 A4G may influence postabsorptive REE independent of changes in body composition, indicating an effect on adaptive thermogenesis 7 Conflicting data have been reported with respect to associations between SNPs in GAD2 and CART and obesity. [18][19][20][21] These opposing findings may partly be due to effects of GAD2 À243 A4G on both energy intake (higher hunger and disinhibition scores) 19 and, based on the present data, increased postabsorptive REE.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This reduction in the energy cost of maintenance is adaptive in that it reduces the rate at which body's tissues are being depleted, and has been demonstrated both in normal-weight subjects (35,(48)(49)(50) as well as in obese individuals (48)(49)(50) . In order to determine whether this adaptive reduction in thermogenesis during weight loss persists during weight recovery, and underlies the disproportionately greater rate of recovery of fat mass relative to FFM, the dynamic changes in body composition and BMR of the thirty-two Minnesota men who completed the 24 weeks of semi-starvation and first 12 weeks of restricted refeeding were re-analysed.…”
Section: Suppressed Thermogenesis: Feedback Signals From Fat Tissuementioning
confidence: 99%
“…Energy restriction induces a reduction in REE below predicted values, as based on the new body composition reached after underfeeding-induced weight loss. [16][17][18][19] The REE reduction in obese subjects losing 10-20% of initial weight, adjusted for changes in body composition, ranges between 3 and 6% of the initial TEE value. Van Gemert et al 20 observed in morbid obese subjects losing on average one-third of initial weight, an average reduction of 7% at 1 year after the start of weight loss and of 4% when weight loss was maintained for more than 3 years.…”
Section: Changes In Food Intake and Energy Expenditurementioning
confidence: 99%